2004
DOI: 10.1079/phn2003589
|View full text |Cite
|
Sign up to set email alerts
|

Diet, nutrition and the prevention of dental diseases

Abstract: Oral health is related to diet in many ways, for example, nutritional influences on craniofacial development, oral cancer and oral infectious diseases. Dental diseases impact considerably on self-esteem and quality of life and are expensive to treat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
639
3
56

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 701 publications
(711 citation statements)
references
References 131 publications
13
639
3
56
Order By: Relevance
“…A study of 5–6‐year‐olds in Kathmandu Valley found that 69% had dental caries (Subedi et al . 2011), and reduction of sugar intake is an important means to reduce such high caries prevalence (Moynihan & Petersen 2004). …”
Section: Discussionmentioning
confidence: 99%
“…A study of 5–6‐year‐olds in Kathmandu Valley found that 69% had dental caries (Subedi et al . 2011), and reduction of sugar intake is an important means to reduce such high caries prevalence (Moynihan & Petersen 2004). …”
Section: Discussionmentioning
confidence: 99%
“…There was no effect of the school intervention status when controlling for baseline level and socio-economic effects for obvious decay experience. [2] Decay into dentine (D 3cv ) at baseline and 24-month follow-up…”
Section: The Assessment Of Obvious Decay Experience [1] D 3cv Mft At mentioning
confidence: 99%
“…Sugars are undoubtedly the most important dietary factor in the development of dental caries (1)(2)(3)(4)(5)(6)(7)(8) and dental caries is the most common chronic disease in the world (9) . Treating caries is responsible for 6-10 % of total health costs, even though there has been a decline in dental caries levels in many countries (10,11) .…”
mentioning
confidence: 99%